Anthocyanins from purple passion fruit (Passiflora edulia Sims) rind—An innovative source for nonbleachable pigment production. Issue 7 (22nd June 2021) - Liu, Jiaman; Teng, Bo; Zhang, Xiaofeng; Dai, Minghui; Lin, Yue; Liu, Yang; McRae, Jacqui M.
Abstract : Abstract: Passion fruit rind is a waste product from the beverage industry that is rich in anthocyanins that can be potentially applied as a natural colorant. However, the inherent instability of anthocyanins causes rapid discoloration. In this study, the cyanidin‐3‐glucoside (C‐3‐G) in passion fruit rind was extracted using 50% ethanol and converted into nonbleachable pigments by reaction with Oolong tea extracts and acetaldehyde. Reactions over 70 days formed high concentrations of stable nonbleachable pigments (3.07–6.68 absorbance unit [A.U.], in total) such as pyranoanthocyanins, as well as oligomeric and polymeric pigments with ethyl‐linked bridges. In C‐3‐G and acetaldehyde reaction, positive relations were found among acetaldehyde concentration, color density, and nonbleachable pigment concentrations. As for reactions with C‐3‐G and Oolong tea extract combined with acetaldehyde, greater color density and greater concentrations of nonbleachable pigments (10.80–12.34, 4.25–4.40 A.U., respectively) were formed compared with acetaldehyde alone. In addition, the antioxidant capabilities of the extracts were enhanced after reaction with Oolong tea extracts. The results of this study show a useful method to enhance the stability of anthocyanins from passion fruit rind and also provide greater economic value to this waste product. Practical Application: Ripened passion fruits contain a high concentration of anthocyanins in their rind. These anthocyanins can be optimally extracted by ultrasonic assisted solvent extraction to provide stable pigments by inducing acetaldehyde (a volatile compound often found in foods and beverages) into the anthocyanins. These stable pigments have a greater reddish hue in solution than the anthocyanin extracted from the rind and are more stable over a greater pH range. In addition, these stable pigments can be potentially used as colorant throughout the food and cosmetic industry to provide high economical values.